The relationship between social support and religiosity on psychological well-being in final year students - Rezeky, Mayang Tri; Ariyanto, Mustaqim Setyo; Khoiryasdien, Andhita Dyorita (International Journal of Health Science and Technology, 2025)
A person is considered as a university student when they enter a college or university. The hardest phase of being a university student is when they enter their final semester because they start working on their final assignments. As final year students in college, they certainly have pressure. The purpose of this study is to determine the effect of social support and religious beliefs of final year students on their psychological well-being. This study employed a quantitative approach with an emphasis on correlation through the distribution of questionnaires. The sample population of this study consisted of final year students, who were usually between 20 and 24 years old. A total of 120 participants were selected for the survey through the nonprobability sampling method. When analyzing the data, the assumption test was used. In this study, the variables of social support, religiosity, and psychological well-being were tested for their hypotheses. The results of the study showed a significance level of 0.000 <0.05. The r square value of psychological well-being gave an effective contribution of 61.55%, and the r square value of psychological well-being gave an effective contribution of 9.55% when combined with social support indicated a strong relationship, which means that there is a relationship between social support and psychological well-being in final year students, but there is no relationship between religiosity and psychological well-being in final year students.